PENGARUH GOOD CORPORATE GOVERNANCE DAN INTELLECTUAL CAPITAL PADA RETURN ON ASSET - Pratama, Gde Setia; Suputra, I Dewa Gede Dharma (E-Jurnal Akuntansi; Vol 10 No 2 (2015), 2015)
The company's performance is the effectiveness of the company's operations are determined based on the objectives to be achieved by the company. This study uses data on banking companies listed in Indonesia Stock Exchange. The samples in this study using purposive sampling method. Data were analyzed with multiple linear regression analysis techniques, because using more than one independent variable. Based on the results of analysis show that managerial ownership, the proportion of independent commissioners, and value added intellectual coefficient effect on return on assets in the banking companies listed in Indonesia Stock Exchange. While institutional ownership does not affect the return on asset.
Keywords: managerial, intellectual, ROA